Product design for manufacture and assembly - Boothroyd, G. (Geoffrey), 1932-; Dewhurst, Peter; Knight, W. A. (Winston Anthony), 1941- (Boca Raton, Fl : CRC Press, 2011)
'Now in its third edition, this volume features new problem sets and student assignments, making this respected reference work now even more suitable for use in product design and design for manufacture courses. Chapters have been updated from previous editions with more recent case studies of the application of design for manufacture and assembly (DFMA) techniques, important industry changes, and emphasis on current trends such as design for power injection molding and surface mount devices. Each chapter also includes updated cost information on materials, labor, and machine operations'--
Includes bibliographical references and index.
Keywords: Industrial design; Concurrent engineering; Production planning; Product design